Influence Of Digital Transformation, Training, Entrepreneurial Knowledge On MSME Performance After The Pandemic - Wahdi, Hilmy; Rivai , VeithZainalzal; Suprapto, Suprapto; Nurhayati, Mafizatun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2024)
This lstudy laims lto lexamine lthe leffect lof ldigital ltransformation, ltraining, lentrepreneurial lknowledge lon lthe lperformance lof lMSMEs lafter lthe lpandemic. lThis lresearch lis lusing lquantitative lresearch. lThe lsample lin lthis lstudy lused lthe lquota lsampling ltechnique lwhere lthe lresearcher lonly lused l100 lpeople las lthe lresearch lsample. lThe ldata lin lthis lstudy lwere lobtained lthrough lquestionnaires ldistributed lvia lgoogle lform. lThe lscale lof lthe lquestionnaire lquestions luses la lLikert lscale lwith la lscore lof l5,4,3,2,1. lThe lcollected ldata lis lthen lanalyzed lby lmultiple lregression lanalysis lthrough l3 lstages, lnamely linstrument ltesting, lclassical lassumption ltesting land lhypothesis ltesting. lThe ltest lresults lshow lthat lall litems lof lthe linstrument lare lvalid land lreliable land lmeet lthe lprerequisites lfor lthe lclassical lassumption ltest. lThe lresults lshowed lthat l1) lDigital ltransformation lhad la lsignificant lpositive leffect lon lMSME lperformance lduring lthe lpandemic, l2) ltraining lhad la lsignificant lpositive leffect lon lMSME lperformance lduring la lpandemic, land l3) lentrepreneurial lknowledge lhad la lsignificant lpositive leffect lon lMSME lperformance lduring la lpandemic land l4) ldigital ltransformation, ltraining land lentrepreneurial lknowledge lhave la lsimultaneous leffect lon lthe lperformance lof lMSMEs lduring lthe lpandemic. lOther lresearchers lwho lwant lto lexamine lmore ldeeply lrelated lto lthe ltopic lin lthis lstudy lcan luse la llarger lsample lsize lwith lmore lvaried lvariables lin lorder lto lobtain lbetter lfindings.